2018
DOI: 10.1111/and.12949
|View full text |Cite
|
Sign up to set email alerts
|

Sperm fluorescent in situ hybridisation study of interchromosomal effect in six Tunisian carriers of reciprocal and Robertsonian translocations

Abstract: Carriers of structural chromosomal anomalies, translocations and inversions are at increased risk of aneuploid gametes production. Besides the direct effect on the involved chromosomes, these rearrangements might disturb the segregation of other structurally normal chromosomes during meiosis. Such event is known as interchromosomal effect. In this study, six male carriers of translocations, four reciprocals and two Robertsonians, were investigated. In addition, seven fertile men with normal 46,XY karyotypes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
3
1
0
2
Order By: Relevance
“…The frequency of disomy for 15 chromosomes (1-3, 5-7, 9, 11, 12, 15, 19, 21, 22, X, and Y) was significantly higher than that in normozoospermic men, with the highest frequency observed for disomy 21, followed by that for 19, 22, 5, the sex chromosomes, and chromosomes 2, 9, 1, 15, 3, 20, 12, 4, 6, and 11. Our results are consistent with those of previous studies analyzing the frequency of disomy for chromosomes 18, 21, X, and Y, all of which showed a significant increase in the frequency of disomy for the sex chromosomes (Baccetti et al, 2005;Godo et al, 2015;Wang et al, 2017) and chromosome 21 (Mahjoub et al, 2011;Vozdova et al, 2013;Hajlaoui et al, 2018) and a nonsignificant increase in the frequency of disomy for chromosome 18 (Machev et al, 2005;Douet-guilbert et al, 2005;Baccetti et al, 2005;Ogur et al, 2006;Chen et al, 2007;Kekesi et al, 2007;Wang et al, 2017;Olszewska et al, 2021).…”
Section: The Interchromosomal Effect (Ice)supporting
confidence: 93%
See 2 more Smart Citations
“…The frequency of disomy for 15 chromosomes (1-3, 5-7, 9, 11, 12, 15, 19, 21, 22, X, and Y) was significantly higher than that in normozoospermic men, with the highest frequency observed for disomy 21, followed by that for 19, 22, 5, the sex chromosomes, and chromosomes 2, 9, 1, 15, 3, 20, 12, 4, 6, and 11. Our results are consistent with those of previous studies analyzing the frequency of disomy for chromosomes 18, 21, X, and Y, all of which showed a significant increase in the frequency of disomy for the sex chromosomes (Baccetti et al, 2005;Godo et al, 2015;Wang et al, 2017) and chromosome 21 (Mahjoub et al, 2011;Vozdova et al, 2013;Hajlaoui et al, 2018) and a nonsignificant increase in the frequency of disomy for chromosome 18 (Machev et al, 2005;Douet-guilbert et al, 2005;Baccetti et al, 2005;Ogur et al, 2006;Chen et al, 2007;Kekesi et al, 2007;Wang et al, 2017;Olszewska et al, 2021).…”
Section: The Interchromosomal Effect (Ice)supporting
confidence: 93%
“…The frequency of nullisomy for 13 chromosomes (3, 4, 6, 9, 11, 12, 16, 19-22, X, and Y) was significantly higher than that in normozoospermic men. Our results are consistent with those of previous studies in which significantly higher frequencies of sex chromosome nullisomy were observed (Ogur et al, 2006;Wang et al, 2017) and nullisomy 22 (Hajlaoui et al, 2018) and inconsistent with those of previous studies that reported significantly higher frequency of nullisomy 18 (Mahjoub et al, 2011;Vozdova et al, 2013;Hajlaoui et al, 2018). The aneuploidy rate was significantly higher than that in normozoospermic men, for all chromosomes, except for chromosomes 10, 17, and 18.…”
Section: The Interchromosomal Effect (Ice)supporting
confidence: 79%
See 1 more Smart Citation
“…Около 2 % мужчин с бесплодием являются носителями структурных хромосомных аномалий [53][54][55]. Наиболее частыми структурными вариантами являются робертсоновские транслокации (0,7-0,9 %) [53,55], реципрокные транслокации (0,6 %) и инверсии (0,2 %) [53].…”
Section: анеуплоидия в сперматозоидах у мужчинносителей структурных аномалий хромосомunclassified
“…Как правило, сбалансированные хромосомные аномалии у мужчин обнаруживают случайно, при цитогенетическом обследовании по поводу повторных выкидышей у супруги, рождения ребенка с хромосомными аномалиями или первичного бесплодия [55,56]. Носители этих хромосомных перестроек фенотипически нормальны (здоровы), но имеют высокий или повышенный риск нарушения фертильности из-за образования анеуплоидных гамет [55][56][57].…”
Section: анеуплоидия в сперматозоидах у мужчинносителей структурных аномалий хромосомunclassified